The utilization of cranial models created using rapid prototyping techniques in the development of models for navigation training - Waran, V.; Pancharatnam, D.; Thambinayagam, H.C.; Raman, R.; Rathinam, A.K.; Balakrishnan, Y.K.; Tung, T.S.; Rahman, Z.A. (2013)
Introduction: Navigation in neurosurgery has expanded rapidly; however, suitable models to train end users to use the myriad software and hardware that come with these systems are lacking. Utilizing three-dimensional (3D) industrial rapid prototyping processes, we have been able to create models using actual computed tomography (CT) data from patients with pathology and use these models to simulate a variety of commonly performed neurosurgical procedures with navigation systems.